1997
DOI: 10.1161/01.res.81.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Upregulates Endothelial Nitric Oxide Synthase Gene Expression in Fetal Pulmonary Artery Endothelium

Abstract: NO, produced by endothelial NO synthase (eNOS), is a key mediator of pulmonary vasodilation during cardiopulmonary transition at birth. The capacity for NO production is maximal at term because pulmonary eNOS expression increases during late gestation. Since fetal estrogen levels rise markedly during late gestation and there is indirect evidence that the hormone enhances nonpulmonary NO production in adults, estrogen may upregulate eNOS in fetal pulmonary artery endothelium. Therefore, we studied the direct ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
181
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(199 citation statements)
references
References 34 publications
15
181
0
3
Order By: Relevance
“…23 In this context, it is interesting to note that estradiol has also been shown to activate Akt signaling, suggesting one possible mechanism for modulation of EPCs. 33 Given the above findings, the central role of Akt signaling in eNOS activity and the regulation of eNOS and NO by estradiol, 34,35 we considered the possibility that EPC mobilization by estradiol might require NO-mediating signaling. We evaluated reendothelialization and EPC kinetics after the injury in eNOS Ϫ/Ϫ mice and found that the absence of eNOS essentially nullified estradiol-induced mobilization of EPCs and blocked the acceleration of endothelial recovery seen in wild-type mice treated with estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…23 In this context, it is interesting to note that estradiol has also been shown to activate Akt signaling, suggesting one possible mechanism for modulation of EPCs. 33 Given the above findings, the central role of Akt signaling in eNOS activity and the regulation of eNOS and NO by estradiol, 34,35 we considered the possibility that EPC mobilization by estradiol might require NO-mediating signaling. We evaluated reendothelialization and EPC kinetics after the injury in eNOS Ϫ/Ϫ mice and found that the absence of eNOS essentially nullified estradiol-induced mobilization of EPCs and blocked the acceleration of endothelial recovery seen in wild-type mice treated with estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Having previously shown that estrogen up-regulation of eNOS expression is ER dependent (33), and that estrogen modifies ERa and ERb abundance in primary fetal pulmonary artery endothelial cells (34), the impact of E 2 on lung estrogen receptor expression was assessed by immunoblot analysis (see Figure E5). ERb protein was detected in 125 days gestation control lung, and the level of expression did not change between 125 days and 140 days gestation; ERa protein was not detected (data not shown).…”
Section: Effect Of E 2 On Pulmonary Nos and Ermentioning
confidence: 99%
“…Estrogen can activate eNOS through a PI3K and Akt mediated nongenomic pathway, causing rapid generation of NO, with beneficial effects on the vasculature (10). Prolonged estrogen exposure also upregulates the expression of eNOS through a genomic pathway, ensuring long-term NO availability (11). Apart from being a potent vasodilator, NO exerts an antiinflammatory role on the endothelium, as manifested by decreased leukocyte recruitment and scavenging of reactive oxygen species (ROS) (12).…”
Section: Estrogen and Nitric Oxidementioning
confidence: 99%